Primary trabecular neuroendocrine tumor (carcinoid) of the ovary: a clinical case report - Andreika, Linas; Rudaitis, Vilius (Lietuvos chirurgija, 2017)
Primary neuroendocrine tumors (carcinoid) of the ovary are very rare neoplasms. They are subdivided into four categories: insular (isolated), trabecular, strumal and mucinous. Trabecular type is one of the least common. It is not associated with carcinoid syndrome and has a good survival rate. We present a case of a 36 years old woman who was diagnosed with a left ovary well differentiated trabecular neuroendocrine tumor and a right ovary mucinous cystadonema. The diagnosis was made after a left ovary biopsy was taken during a laparoscopic cystectomy of the right ovary. Immunohistochemical staining showed positivity for Chromogranin A, Synaptophysin and Ki67 proliferation index was >5%. A laparoscopic left salpingoovarectomy, myomectomy, omentum biopsy, left pelvic and paraaortic lymphadenectomy was performed for surgical staging purposes. The final hystological examination showed no signs of the neuroendocrine tumor. A thorough inspection of an organ system during surgery led to an incidental detection of a small but life threatening neuroendocrine tumor and full patient examination. 1 year after the diagnosis was established there are no signs of disease progression.